Bright Light Therapy and Circadian Cycles in Institutionalized Elders - Rubiño, José A.; Gamundí, Antoni; Akaarir, Mourad; Canellas, Francesca; Rial, Rubén; Nicolau, M. Cristina (Frontiers in Neuroscience, 2020)
Background Bright light therapy has been found to be an efficient method to improve the main parameters of circadian rhythms. However, institutionalized elders may suffer reduced exposure to diurnal light, which may impair their circadian rhythms, cognitive performance, and general health status. Objectives To analyze the effects of 5 days of morning exposure for 90 min to bright light therapy (BLT) applied to institutionalized elderly subjects with mild/moderate cognitive impairment. Subjects Thirty-seven institutionalized subjects of both sexes, aged 70–93 years. Methods The study lasted three consecutive weeks. During the second week the subjects were submitted to BLT (7000–10,000 lux at eye level) on a daily basis. Cognition, attention, and sleep quality were evaluated at the beginning of the first and third week. Circadian variables were recorded continuously throughout the 3 weeks. Non-invasive holders and validated tests were used to analyze the variables studied. Results After BLT we have found significant improvements in general cognitive capabilities, sleep quality and in the main parameters of the subject’s circadian rhythms. The results show that merely 90 min of BLT for five days seems to achieve a significant improvement in a constellation of circadian, sleep, health, and cognitive factors. Conclusion Bright light therapy is an affordable, effective, fast-acting therapy for age-related disturbances, with many advantages over pharmacological alternatives. We hypothesize these effects were the result of activating the residual activity of their presumably weakened circadian system.